2017
DOI: 10.1038/s41598-017-17120-8
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of cellular osteogenic differentiation through daily stimulation time based on polypyrrole planar electrodes

Abstract: In electrical stimulation (ES), daily stimulation time means the interacting duration with cells per day, and is a vital factor for mediating cellular function. In the present study, the effect of stimulation time on osteogenic differentiation of MC3T3-E1 cells was investigated under ES on polypyrrole (Ppy) planar interdigitated electrodes (IDE). The results demonstrated that only a suitable daily stimulation time supported to obviously upregulate the expression of ALP protein and osteogenesis-related genes (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 41 publications
1
28
1
Order By: Relevance
“…ALP activity for ADSCs+DIF+ES at Day 14 was 3.6 fold and 2.7 fold higher than the peak value of ADSCs+GRO+ES and ADSCs+DIF, respectively. Not surprisingly, ALP expression for ADSCs+GRO+ES was similar to that for ADSCs+DIF, indicating an inductive effect of ES and graphene on osteogenic differentiation, independent of other inducers, which is consistent with previous reports [7,15]. Statistical analysis revealed that both ES (F (2, 60) = 75.08, P < 0.0001) and day (F (3, 60) = 43.13, P < 0.0001) significantly affected ALP activity within ADSCs, as well as the interaction between ES and day (Overall two-way ANOVA, F (6, 60) = 24.12, P < 0.0001).…”
Section: Effect Of Es On Proliferation and Osteogenic Differentiationsupporting
confidence: 92%
See 2 more Smart Citations
“…ALP activity for ADSCs+DIF+ES at Day 14 was 3.6 fold and 2.7 fold higher than the peak value of ADSCs+GRO+ES and ADSCs+DIF, respectively. Not surprisingly, ALP expression for ADSCs+GRO+ES was similar to that for ADSCs+DIF, indicating an inductive effect of ES and graphene on osteogenic differentiation, independent of other inducers, which is consistent with previous reports [7,15]. Statistical analysis revealed that both ES (F (2, 60) = 75.08, P < 0.0001) and day (F (3, 60) = 43.13, P < 0.0001) significantly affected ALP activity within ADSCs, as well as the interaction between ES and day (Overall two-way ANOVA, F (6, 60) = 24.12, P < 0.0001).…”
Section: Effect Of Es On Proliferation and Osteogenic Differentiationsupporting
confidence: 92%
“…The following day, the devices with cells were subjected to 1 h symmetric biphasic square pulses at 0 V/cm, 1 V/cm, 10 V/cm and 20 V/cm with phase duration of 1 s and interphase interval of 200 ms, respectively. The ES settings were based on previously published research [14,15], with biphasic stimulation chosen to prevent excessive charge accumulation at the electrodecell/tissue interface that could result in cell/tissue damage [26,27]. In addition, excessive charge accumulation at the electrodes can hinder the flow of current from the stimulating electrodes [28].…”
Section: Optimization Of Applied Voltage For Esmentioning
confidence: 99%
See 1 more Smart Citation
“…Several extracellular factors are also activated and enter cells with Ca 2+ through a switch on the cell membrane. Moreover, Ca 2+ further binds to calmodulin and activates the Ca 2+ signaling transduction pathway to regulate the expression of osteogenesis‐related genes, consequently inducing osteogenic differentiation . However, the low Ca 2+ concentration difference between the intracellular and extracellular environment makes an electrical signal alone insufficient to produce significant bone regeneration in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, these biomaterials take advantage of the effect of a direct current (DC) or an electrical field on both cell proliferation and differentiation, stimulating, for instance, the regeneration of muscles, organs, and/or bones [3][4][5][6][7][8]. Moreover, ES has been studied as a potential tool in tissue regeneration to increase the proliferation and differentiation of human stem cells [5,[9][10][11][12][13]. There are several reports in the literature on the use of ES for fracture treatments and tissue repairs using electrical stimulation methodologies, particularly DC or electromagnetic fields [14].…”
Section: Introductionmentioning
confidence: 99%